WXJ-202, a novel Ribociclib derivative, exerts antitumor effects against breast cancer through CDK4/6 - Ji, Jing; Liu, Wenwen; Xu, Yuxin; Xu, Zhou; Lv, Mingxiao; Feng, Jing; Lv, Jinyu; He, Xingbei; Zhang, Zhen; Xie, Mengru; Jing, Aixin; Wang, Xiujun; et al. (Frontiers in Pharmacology, 2023)
Cyclin-dependent kinases 4 and 6 (CDK4/6) are key regulatory proteins in the cell division and proliferative cycle in humans. They are overactive in many malignant tumors, particularly in triple-negative breast cancer (TNBC). Inhibition of CDK4/6 targets can have anti-tumor effects. Here, we designed and synthesized a novel derivative of Ribociclib that could affect CDK4/6, named WXJ-202. This study aimed to investigate the effects of compound WXJ-202 on proliferation, apoptosis, and cell cycle arrest in human breast cancer cell lines and their molecular mechanisms. We assayed cell viability with methyl thiazolyl tetrazolium (MTT) assay. Clone formation, migration, and invasion ability were assayed by clone formation assay, wound healing assay, and transwell invasion assay. The effect of compound WXJ-202 on apoptosis and cell cycle was detected by flow cytometry analysis. Western blotting was performed to detect the expression of proteins related to the CDK4/6-Rb-E2F pathway. The anti-cancer effects were studied in vivo transplantation tumor models. WXJ-202 was shown to inhibit cell proliferation, colony formation, migration, and invasion, as well as induce apoptosis and cycle arrest in breast cancer cells. The levels of proteins related to the CDK4/6-Rb-E2F pathway, such as CDK4, CDK6, and p-Rb, were decreased. Finally, studies had shown that compound WXJ-202 exhibited significant anti-tumor activity in transplantation tumor models. In this research, the compound WXJ-202 was shown to have better anti-tumor cell proliferative effects and could be used as a potential candidate against TNBC tumors.